EVALUASI PERSENTASI KESESUAIAN DENGAN PEDOMAN 3 PENGGUNAAN ANTIBIOTIK DAN ANTIVIRUS PADA PASIEN COVID-19 NON VENTILATOR DI RSUD BANGIL - Vincentina Yenny Triamyanti; Rika yulia; fauna herawati; Abdul Kadir Jaelani (LPPM Akafarma Sunan Giri Ponorogo, 2022)
Coronavirus (Covid-19) is an infectious disease caused by the SARS-CoV-2 virus. Most people infected with this virus develop mild to moderate respiratory illness and recover without requiring special treatment. However, people who are older and have comorbid will experience severe illness and require medical attention that can lead to death. The aimed of this study was to provide an overview of the evaluation of the use of antibiotics and antivirals in non-ventilated Covid-19 patients at Bangil Hospital. The method used is Defined Daily Dose (DDD/100 patient-days) and One Way ANOVA analysis. Based on the DDD/100 patient-days value, the most widely used antibiotic group was Moxifloxacin and the most common antiviral group was Remdesivir. Meanwhile, based on different tests on the use of antibiotics and antivirals, it is known that there is no significant difference between those who use antibiotics and do not use antibiotics and those who use antivirals without using antivirals. Thus it can be concluded that the use of antibiotics and antivirals has no effect on the patient's recovery rate.